Endometrial stromal cell proteome mapping in repeated implantation failure and recurrent pregnancy loss cases and fertile women. Issue 3 (March 2019) - Dhaenens, Lien; Lierman, Sylvie; De Clerck, Laura; Govaert, Elisabeth; Deforce, Dieter; Tilleman, Kelly; De Sutter, Petra
Abstract: Research question: Are there proteomic differences between endometrial stromal cells of repeated implantation failure (RIF), recurrent pregnancy loss (RPL) and normal fertile women, and is there differential protein expression upon decidualization? Design: This exploratory study investigated the proteome of in-vitro cultured endometrial stromal cells of women with RIF ( n  = 4), women with RPL ( n  = 3) and normal fertile women ( n  = 4), comparing day 0 with 5 days of decidualization. Total proteins extracted from cell lysates were analysed by high-definition mass spectrometry. Data analysis was performed using significance analysis of microarray in R ( P  < 0.05; false discovery rate [FDR] 10%). Results: In the RIF group, ANXA6, PSMC5 and FSCN1 were up-regulated (1.9-fold, 2.5-fold and 1.9-fold, respectively), whereas PBXIP1 was down-regulated (7.7-fold) upon decidualization. In the RPL group, RPS25 and ACADVL were down-regulated (1.9-fold and 2.4-fold, respectively; FDR 10%) between the non-decidualized and the decidualized samples. In the normal fertile group VIM and RPL23A were down-regulated (1.9-fold and 2.4-fold, respectively). Comparing ratios of expression of decidualized over non-decidualized samples in the different groups revealed six differentially expressed proteins: DUX4L2, CNPY4, PDE7A, CTSK, PCBP2 and PSMD4. Comparison of RPL versus normal fertile in the decidualized condition revealed serotransferrin to be differentially expressed. The changes in expression levels for serotransferrin, ANX6, ACDVL and VIM were confirmed by western blot. Conclusions: Results show a varying response of endometrial stromal cells in distinct clinical groups (RIF, RPL and normal fertile) upon in-vitro decidualization. Serotransferrin could serve as a marker for the aberrant decidualization process in RPL.